Association between self-perception of the neighborhood environment and sleep problems in older Brazilian adults: findings from ELSI-Brazil - Daiana Vieira Sutil; Bruno de Souza Moreira; Jaquelini Betta Canever; Letícia Martins Cândido; Ana Lúcia Danielewicz; Maria Fernanda Lima-Costa; Núbia Carelli Pereira de Avelar (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: This study aimed to investigate associations between neighborhood perception and sleep problems in older Brazilian adults. A cross-sectional study was conducted with 5,719 community-dwelling older adults (≥ 60 years) from the Brazilian Longitudinal Study of Aging (ELSI-Brazil, 2019-2021). The outcomes were self-reported sleep problems: poor sleep quality, daytime sleepiness, primary insomnia complaints, difficulty staying asleep, and waking up at dawn. The exposure variables were questions about the perception of participants about the physical and social environment of the neighborhood. Logistic regression was used in data analysis. Garbage, rubbish, or tall grass on the streets and the desire to move were associated with higher odds of poor sleep quality. Concern about falling due to damaged sidewalks, concern about having difficulties taking transportation, and concern about having difficulties crossing the street were associated with higher odds of all sleep problems. Sound/noise of buses and cars was associated with higher odds of some sleep problems. Perceiving the neighborhood as a good place to live was associated with lower odds of daytime sleepiness and primary insomnia complaints. Trusting most people in the neighborhood and perceiving that kids and younger people treat adults with respect were associated with lower odds of daytime sleepiness, primary insomnia complaints, and waking up at dawn. Being a good place for kids to play and raise teenagers was associated with lower odds of daytime sleepiness. These results can assist public administrators in creating urban planning policies aimed at improving neighborhood environments as a means of health promotion.